Enhanced Osteoinductive Bone Repair Using Dual Growth Factors (VEGF and BMP-2) with Alendronate in Engineered Hydroxyapatite Scaffold - Intan Maslina Musa; Mohd Riduan Mohamad; Nur Nabilah Abu Bakar; Nadia Mohd Effendy; Ka Liong Tan; Amira Raudhah Abdullah (Bentham Science Publishers Ltd., 2026)
Indexed by WOS/ERA